Twenty-Five Novel Loci for Carotid Intima-Media Thickness: A Genome-Wide Association Study in >45 000 Individuals and Meta-Analysis of >100 000 Individuals. Issue 4 (2nd December 2021) - Yeung, Ming Wai; Wang, Siqi; van de Vegte, Yordi J.; Borisov, Oleg; van Setten, Jessica; Snieder, Harold; Verweij, Niek; Said, M. Abdullah; van der Harst, Pim
Abstract : Objective: Carotid artery intima-media thickness (cIMT) is a widely accepted marker of subclinical atherosclerosis. Twenty susceptibility loci for cIMT were previously identified and the identification of additional susceptibility loci furthers our knowledge on the genetic architecture underlying atherosclerosis. Approach and Results: We performed 3 genome-wide association studies in 45 185 participants from the UK Biobank study who underwent cIMT measurements and had data on minimum, mean, and maximum thickness. We replicated 15 known loci and identified 20 novel loci associated with cIMT at P <5×10 −8 . Seven novel loci ( ZNF385D, AD AMTS9, EDNRA, HAND2, MYOCD, ITCH/EDEM2/MMP24, and MRTFA ) were identified in all 3 phenotypes. An additional new locus ( LOXL1 ) was identified in the meta-analysis of the 3 phenotypes. Sex interaction analysis revealed sex differences in 7 loci including a novel locus ( SYNE3 ) in males. Meta-analysis of UK Biobank data with a previous meta-analysis led to identification of three novel loci ( APOB, FIP1L1, and LOXL4 ). Transcriptome-wide association analyses implicated additional genes ARHGAP42, NDRG4, and KANK2 . Gene set analysis showed an enrichment in extracellular organization and the PDGF (platelet-derived growth factor) signaling pathway. We found positive genetic correlations of cIMT with coronary artery disease r g =0.21 ( P =1.4×10 -7 ), peripheral artery disease r g =0.45 ( P =5.3×10 -5 ), and systolic blood pressure r g =0.30 ( P =4.0×10 -18 ). A negative genetic correlation between average of maximum cIMT and high-density lipoprotein was found r g =−0.12 ( P =7.0×10 -4 ). Conclusions: Genome-wide association meta-analyses in >100 000 individuals identified 25 novel loci associated with cIMT providing insights into genes and tissue-specific regulatory mechanisms of proatherosclerotic processes. We found evidence for shared biological mechanisms with cardiovascular diseases.